2020
DOI: 10.1177/0300060520964369
|View full text |Cite
|
Sign up to set email alerts
|

Lung sonography can improve the specificity of determination of left-sided double-lumen tracheal tube position in both novices and experts: a randomised prospective study

Abstract: Objective Lung sonography can be helpful to determine the position of a left-sided double-lumen tube (DLT). However, clinical experience is required for correct assessment. We investigated whether lung sonography can improve the diagnostic efficacy of determining the DLT position in novices and experts. Methods In this randomised prospective clinical study, 88 patients were allocated to two groups using auscultation or lung sonography for initial assessment of the DLT position. In each group, two repeated asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 15 publications
(26 reference statements)
0
12
0
Order By: Relevance
“…Nevertheless, US provides key advantages, including wide availability, ease of use, and significantly decreased exposure to respiratory secretions, thus minimizing operator risk in situations where the patient has transmissible respiratory pathogens [ 22 , 25 ]. This study demonstrated that the time needed for confirmation and adjustment of the LDLT position was significantly shorter when using lung US compared to when using FOB (median time 3 vs. 6 min, respectively), reducing potential exposure time even further.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, US provides key advantages, including wide availability, ease of use, and significantly decreased exposure to respiratory secretions, thus minimizing operator risk in situations where the patient has transmissible respiratory pathogens [ 22 , 25 ]. This study demonstrated that the time needed for confirmation and adjustment of the LDLT position was significantly shorter when using lung US compared to when using FOB (median time 3 vs. 6 min, respectively), reducing potential exposure time even further.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several recent studies have compared US to clinical methods for DLT positioning and found that US significantly increases accuracy of LDLT placement [ 11 , 12 , 19 – 21 ]. The limited training requirements, cost effectiveness, and simplicity of lung ultrasound make it a compelling alternative to clinical assessment for LDLT positioning, but little investigation has been performed to compare US to the current gold standard of FOB [ 22 ]. One small, prospective comparison study demonstrated excellent concordance between FOB and US findings for assessment of LDLT positioning, with analyses of time and cost effectiveness analysis favoring US [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…One study [ 24 ] was excluded because ultrasound examination was carried out after correct placement of DLT, and two [ 25 , 26 ] studies were excluded for not using ultrasound to assess the DLT position. Finally, eight studies [ 14 , 15 , 20 , [27] , [28] , [29] , [30] , [31] ] were included in the quantitative analysis ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Also, Chung et al (11) found that LUS had higher ac-curacy than auscultation for detecting DLT misplacement with experts (69.8% vs. 37.5%). Moreover, Sustic et al (16) reported that LUS had higher accuracy when added to auscultation compared to auscultation alone (88% vs. 72%).…”
Section: Discussionmentioning
confidence: 99%
“…LUS is a noninvasive method that has been widely employed in airway management in the past years and can be used to assess the placement of the endotracheal tube even in an emergency (4,9). Even in thoracic surgery, LUS has shown to be a superior approach and enhances auscultation accuracy for determining the proper placement of DLTs due to its high sensitivity and specificity (10,11). Moreover, LUS is a compelling alternative to FOB because of its simplicity and less required training (12).…”
Section: Introductionmentioning
confidence: 99%